Minimally Interrupted Non-Vitamin K Antagonist Oral Anticoagulants vs. Bridging Therapy and Uninterrupted Vitamin K Antagonists During Atrial Fibrillation Ablation: A Retrospective Single-Center Study - Tang, Lihong; Liu, Haiyan; Deng, Hai; Zhan, Xianzhang; Fang, Xianhong; Liao, Hongtao; Liu, Yang; Fu, Lu; Fu, Zuyi; Liu, Huiyi; Wu, Shulin; Xue, Yumei (Frontiers in Medicine, 2020)
Objectives: Although the latest international guidelines recommend the use of uninterrupted non-vitamin K antagonist oral anticoagulants (NOAC) during atrial fibrillation (AF) ablation, it does not reflect current clinical practice, as most centers still use a minimally interrupted NOAC strategy. The purpose of this study was to evaluate the safety and effectiveness of minimally interrupted NOAC compared with bridging therapy and uninterrupted vitamin K antagonist (VKA) for nonvalvular AF ablation. Patients and Methods: A total of 4520 patients who underwent AF ablation between January 2010 and December 2018 were included in the analysis. According to their periprocedural anticoagulation strategies, patients were divided into three groups: Bridging heparin group (n = 1848); Uninterrupted VKA group (n = 796) and Minimally interrupted NOAC group (Total n = 1876; dabigatran: n = 865; rivaroxaban, n = 1011). A combined complication endpoint (CCE) as composed of any bleeding complications and thromboembolic events was analyzed. Results: Rates of thromboembolisms were similar among the three groups (0.22% for Bridging heparin group, 0.25% for Uninterrupted VKA group, and 0.11% for Minimally interrupted NOAC group, p = 0.626). There was a significant difference among the three groups for the incidence of overall bleeding events (8.50% for Bridging heparin group, 4.52% for Uninterrupted VKA group, and 2.67% for Minimally interrupted NOAC group, p < 0.001). A significant difference of CCE rates was shown in the Minimally interrupted NOAC group as compared with the Uninterrupted VKA group (2.77 vs. 4.77%, p = 0.008) and the Bridging heparin group (2.77 vs. 8.71%, p < 0.001). There was no significant difference in CCE rates among the different NOACs (dabigatran 2.89% vs. rivaroxaban 2.67%, p = 0.773). Conclusions: In patients undergoing AF ablation, minimally interrupted NOACs during the periprocedural period appears safer and equally effective when compared to the bridging heparin and uninterrupted VKA therapy.